EKSISTENSI KEPEMIMPINAN ISLAMI SULTAN AGUNG DAN RELEVANSINYA DENGAN PENDIDIKAN ISLAM DI ERA MODERN - Shidqiyah, Shidqiyah (Reflektika, 2022)
Behind the glory of civilization, there is an inspiring record of leadership that has reached the peak of glory. The land of Java was successful during the reign of Sultan Agung Hanyakrakusuma. He showed his authority and was firm and disciplined in deciding a problem in the Islamic Mataram kingdom. Sultan Agung's character inspired many things, especially in becoming a successful leader. This research includes a literative study (library research), which examines the thoughts of figures from various inspirations and records of their lives through various studies on Sultan Agung, which are then useful for Islamic education in this modern era. The data collection technique is by analyzing various findings of relevant data. The results of this study include several things: First, the character of Sultan Agung includes a great curiosity, firm, wise, forgiving, generous, humble, and patient. Second, efforts to build leadership character like Sultan Agung, namely character building steps, he increases his self-esteem, placing himself in a good environment, being firm, disciplined and alert, dreaming of big things, and highly committed. Third, the characters of Sultan Agung have relevance to current education, namely PERMENDIKBUD No. 20 of 2016 Article 2 Chapter II, regarding Competency Standards for Elementary and Secondary Education Graduates. Then with the second part of the Content Standards of article 6.Â